CONSISTENCY AND MAGNITUDE OF DIFFERENCES IN READING CURRICULUM‐BASED MEASUREMENT SLOPES IN BENCHMARK VERSUS STRATEGIC MONITORING. Issue 3 (5th January 2015) - Mercer, Sterett H.; Keller‐Margulis, Milena A.
<x xml:space="preserve">Abstract</x> Differences in oral reading curriculum‐based measurement (R‐CBM) slopes based on two commonly used progress monitoring practices in field‐based data were compared in this study. Semester‐specific R‐CBM slopes were calculated for 150 Grade 1 and 2 students who completed benchmark (i.e., 3 R‐CBM probes collected 3 times per year) and strategic (i.e., one R‐CBM probe collected monthly) assessments. Slopes based on two adjacent benchmark assessments were positively correlated with slopes based on three monthly strategic assessments in the spring semester of Grade 1 but not in either Grade 2 semester, and significant differences were found between the slopes in all semesters. Consistent with another study showing that slopes are overestimated when single probes are administered per occasion, slopes were larger when based on strategic versus benchmark data in the current study, and the average discrepancies between slopes were greater‐than‐expected growth rates in all semesters. The current findings, based on field‐based data, illustrate the impact of variations in commonly used progress monitoring procedures on the precision of calculated slope estimates.